2009
DOI: 10.3855/jidc.422
|View full text |Cite
|
Sign up to set email alerts
|

Septic shock due to visceral leishmaniasis, probably transmitted from blood transfusion

Abstract: A case of visceral leishmaniasis (VL) in a 77-year-old woman, with renal failure on haemodialysis, admitted in the intensive care unit (ICU) with vascular instability requiring vassopressor treatment, is presented. Initially, no co-infection could be detected. The patient initially responded well when liposomal amphotericin B was administered, after bone marrow demonstrated multiple intra-cellular Leishmania amastigotes and extra-cellular promastigotes. However, the patient died from uncontrolled septic shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…VL is a known opportunistic infection most commonly affecting immunosuppressed individuals, especially HIV patients 12 and less frequently organ transplant recipients 13‐15 . Three possible mechanisms may be responsible for the clinical development of VL: 1) acquisition of Leishmania infection via the bite of an infected sand fly, 16 2) reactivation of a latent infection induced by immunosuppression or acquired immunodeficiency, 17,18 and 3) iatrogenic acquisition of Leishmania infection directly through the transplanted organ or after transfusion of infected blood products 13‐15,19,20 . According to the answers given during the interview, the patient apparently always lived in urban areas considered as nonendemic for leishmaniasis and never had leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…VL is a known opportunistic infection most commonly affecting immunosuppressed individuals, especially HIV patients 12 and less frequently organ transplant recipients 13‐15 . Three possible mechanisms may be responsible for the clinical development of VL: 1) acquisition of Leishmania infection via the bite of an infected sand fly, 16 2) reactivation of a latent infection induced by immunosuppression or acquired immunodeficiency, 17,18 and 3) iatrogenic acquisition of Leishmania infection directly through the transplanted organ or after transfusion of infected blood products 13‐15,19,20 . According to the answers given during the interview, the patient apparently always lived in urban areas considered as nonendemic for leishmaniasis and never had leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…Classically, transmission of Leishmania parasites occurs through sand fly bites, however, studies in France {[7] #248}, Italy {[8] #6}, Spain {[9] #12}, India {[10] #9}, Bangladesh {[11] #250} and Turkey {[12] #251} showed that asymptomatic individuals are found among blood donors, suggesting that transfusion of Leishmania -contaminated blood products might be a source of disease transmission in parallel to syringe sharing {[13] #68} and organ transplantation {[14] #7; [15] #8; [16] #19; [17] #41; [18] #246}. In northeastern Brazil, the prevalence of anti- Leishmania antibodies was 9% among blood donors, increased to 25% in a VL focus and was highest (37%) among poly-transfused hemodialysis patients {[19] #37}.…”
Section: Introductionmentioning
confidence: 99%
“…Transmission of the Leishmania parasite through blood transfusion has not been reported in the United States. However, cases of transfusion‐transmitted L. donovani have been described in several countries . Most of the reports occurred before 1997 and do not contain specific manufacturing details about the transfused blood, but it is unlikely that the blood was leukoreduced.…”
Section: Discussionmentioning
confidence: 99%